2021
DOI: 10.1111/jfpe.13845
|View full text |Cite
|
Sign up to set email alerts
|

Freeze–thawing damage evaluation of vegetables with two cutting orientations

Abstract: This work aimed to evaluate how cut orientation of squash, eggplant, and turnip affects the damage of tissues due to freeze/thawing process. For that, cylinders of 2 cm diameter and 0.5 cm height were cut in two orientations according to vascular tissues: longitudinal and transversal. Then, they were frozen at À20 C for 53 hr and thawed at 6.1 C for 12 hr. After that, two indirect methods to measure tissue damage were analyzed: by electrical conductivity of drip loss and by mass transfer during drying of sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…2) Conductimetría: La conductividad eléctrica se midió tal como lo describe Silva, et al [13] tanto en fresco, como después de descongelado. Para ello se tomaron 3 muestras de arándano por cada método.…”
Section: B Proceso De Descongelaciónunclassified
“…2) Conductimetría: La conductividad eléctrica se midió tal como lo describe Silva, et al [13] tanto en fresco, como después de descongelado. Para ello se tomaron 3 muestras de arándano por cada método.…”
Section: B Proceso De Descongelaciónunclassified
“…For instance, Fan et al (2021) reported that high-power US destroys the cell walls of carrots, forming pore structures and reducing the VFD time by 15%; while Xu, Chen, Sylvain Tiliwa, et al (2021) reported that sequential pretreatment with dual frequency US significantly improves the color, flavor, and nutrient characteristics of freeze-dried strawberry slices. FT is another effective non-thermal pretreatment method that has been widely used for meat products ( Jiang, Nakazawa, Hu, Osako, & Okazaki, 2019 ), fruits and vegetables ( Bassey, Cheng, & Sun, 2022 ; Silva, Ramirez, Gavidia, & Miano, 2021 ). During the FT pretreatment process, the material is cooled, converting the water in the cells to ice crystals, which are then melted upon warming, resulting in more intracellular space and cavities in the cell structure ( Silva et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…FT is another effective non-thermal pretreatment method that has been widely used for meat products ( Jiang, Nakazawa, Hu, Osako, & Okazaki, 2019 ), fruits and vegetables ( Bassey, Cheng, & Sun, 2022 ; Silva, Ramirez, Gavidia, & Miano, 2021 ). During the FT pretreatment process, the material is cooled, converting the water in the cells to ice crystals, which are then melted upon warming, resulting in more intracellular space and cavities in the cell structure ( Silva et al, 2021 ). Xu, Zhang, Feng, et al (2021) reported that FT pretreatment before VFD changes the microstructure of okra and shortens its drying time by 62.5%, and the dry-matter-content loss is only ∼5.6%.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to food structure, the tissues orientation, sample size and tissue distribution should be also considered when those approaches are studied. For instance, cut orientation has been demonstrated to be important in food with complex structures (formed by different tissues), as affecting drying (Ren et al, 2021), shrinkage (Lin et al, 2020;Rojas & Augusto, 2018c), rehydration (De Los Santos et al, 2021) and freezethawing process (Silva et al, 2021). This demonstrates that food material is anisotropic, which means that food properties depend on the orientation of the food when analyzed.…”
mentioning
confidence: 99%